Increased Stress Hyperglycemia Ratio Predicts Poor Clinical Outcome in Critically Ill COPD Patients: A Retrospective Study - Qiao M; Yang H; Qin M; Li Y; Wang H (International Journal of COPD)
Mengyuan Qiao,1,* Hui Yang,2,* Mengzhen Qin,2 Yingyang Li,3 Haiyan Wang2 1School of Nursing, Henan University of Science and Technology, Luoyang, 471023, People’s Republic of China; 2People’s Hospital of Xinjiang Uygur Autonomous Region, Urumqi, 830001, People’s Republic of China; 3The First Affiliated Hospital of Henan University of Science and Technology, Luoyang, 471003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haiyan Wang, People’s Hospital of Xinjiang Uygur Autonomous Region, Urumqi, 830001, People’s Republic of China, Email 15660638558@163.comObjective: Stress hyperglycemia ratio (SHR) was introduced as an indicator of relative hyperglycaemia and is widely used for prognostic prediction in critically ill patients. The present study aimed to investigate the relationship between SHR and adverse clinical outcomes in critically ill COPD patients.Methods: A total of 1,580 patients diagnosed with COPD were included in this retrospective cohort study. SHR = ABG (mmol/L) / [1.59 × HbA1c (%) - 2.59]. Primary endpoints included ICU mortality and in-hospital mortality. Secondary endpoints were acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and acute respiratory failure (ARF). Logistic regression, Restricted Cubic Sample (RCS) and Receiver Operating Characteristic (ROC) were used to explore the relationship between SHR and prognosis of COPD patients. In addition, subgroup analyses and interaction tests were performed to investigate potential heterogeneity.Results: Multivariate logistic regression analysis showed that elevated SHR was not associated with ICU mortality and in-hospital mortality. In contrast, SHR quartiles were correlated with ICU mortality and in-hospital mortality. Restricted cubic spline regression models showed a nonlinear correlation between SHR and both ICU mortality and in-hospital mortality (all P< 0.001). In addition, a linear correlation was found between SHR and AECOPD and ARF, with elevated SHR associated with increased risk of AECOPD and ARF. ROC analyses showed that SHR was a more effective predictor of mortality and prognosis than admission blood glucose (ABG) and hemoglobin A1c (HbA1c) in patients with COPD, with the former being a better predictor of mortality and prognosis. In subgroup analyses, after adjusting for all covariates considered in the present study, the relationship between SHR and prognostic risk in patients with COPD remained stable across gender, age, BMI, smoking, drinking, history of hypertension, coronary heart disease, diabetes, and cerebrovascular disease.Conclusion: SHR is independently associated with an increased risk of adverse clinical outcomes in critically ill COPD patients.Keywords: stress hyperglycemia ratio, COPD, mortality, AECOPD, ARF